Israf dan Pendidikan Islam Sebagai Pencegahnya - M. Arif Idris (Program Studi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2018)
Israf is one of the acts that are forbidden by Islam. Israf comes from Arabic, meaning it is beyond the limit. People do Israf called musrif. The plural is musrifun or musrifun. Broadly speaking, Israf can be understood as using something that crosses the limits that are appropriate according to Islamic teachings. Israf is a disgraceful act, which brings great harm and is not liked by Allah SWT. The forms of Israf are found in several parts. Among them: Israf’s behavior in eating and drinking. Israf in dress, Israf’s behavior in dress. One of the prevention of Israf is through education